PENINGKATAN KEMAMPUAN GURU BAHASA INGGRIS PADA DESAIN PRESENTASI MATERI SEBAGAI PENDUKUNG MEDIA PEMBELAJARAN - Firdania, Milda; Prihartini, Narti; Marselia , Maya (Prosiding Seminar Hasil Penelitian dan Pengabdian Kepada Masyarakat (SEHATI ABDIMAS), 2024)
Subject teachers need to develop their abilities in technology in order to continue to update their teaching methods, especially in creating learning media. The High School English Subject Teacher Conference (MGMP) in Sambas Regency, West Kalimantan Province, in this case also requires developing the ability to use software that can be used to create attractive learning media. So far, the digital technology-based learning media used for presentations by English MGMP teachers in Sambas when teaching in class is PowerPoint slides, this is due to teachers’ limitations in mastering the software for creating presentation designs. The aim of this service activity is to empower teachers who are members of the English MGMP in Sambas by increasing their competency in creating attractive learning media designs using Canva. Canva is software or application that really supports the creation of learning media with various templates and complete features. Based on the problems of these teachers, systematic education is needed to be able to make learning media attractive and practical so that it can be implemented by teachers in teaching and learning activities. The findings from this community service activity were that the teachers involved gained new knowledge to create learning media presentation designs through Canva. In conclusion, this activity has a positive impact on teachers in improving their ability to use technology, especially technology in the world of design.